Особенности белкового обмена у высокопродуктивных глубокостельных коров в разные сезоны года - Корейба, Людмила Володимирівна; Koreyba, Ludmila; Koreyba, L. V.; Koreyba, Lyudmila Volodymyrivna; Koreyba, L.; Koreiba, L. V.; Coregba, L. V.; Дуда, Юлія Вікторівна; Duda, Yuliya; Duda, Y. V.; Duda, J. V.; Duda, Julia; et al. (Житомирський нац. агроекологічн. ун-т, 2019)
Изучение обмена веществ в организме коров, в зависимости от физиологического состояния, факторов кормления и условий содержания в разные сезоны года является необходимым условием направленного воздействия на их воспроизводительную способность и продуктивность. В частности, научный и практический интерес представляет раскрытие физиолого-биохимических механизмов, с которыми связаны особенности обмена веществ в организме коров в течение беременности. Цель работы заключалась в изучении особенностей белкового обмена у высокопродуктивных глубокостельных коров в разные сезоны года. Объектом для исследования послужили коровы с молочной продуктивностью 5–6 тыс. кг за лактацию на 8–9-ом месяце беременности и отобранные у них образцы крови. Биохимическое исследование плазмы крови коров проводили по общепринятым методикам. Установлено, что сезонные изменения белкового обмена глубокостельных коров имели циклический характер. В зимний период в плазме крови коров наблюдали снижение содержания глобулинов (за счет a-, b и γ-глобулинов) по сравнению с летним, что характеризует высокую активность белкового обмена в летний период со спадом в зимнее время. У сухостойных коров содержание альбуминов и белковый коэффициент достигали максимума зимой с достоверным снижением их весной и летом, а осенью они снова начинали подниматься. Степень и направленность изменений активности АЛТ и АСТ подобны сезонным изменениям содержания альбуминов, что свидетельствует о низкой интенсивности белоксинтезирующих процессов в печени в летнее время. Вивчення обміну речовин в організмі корів, в залежності від фізіологічного стану, факторів годівлі та умов утримання в різні сезони року, є необхідною умовою направленої дії на їх відтворювальну здатність і продуктивність. А саме, науковий і практичний інтерес представлений розкриттям фізіологобіохімічних механізмів, з якими пов’язані особливості обміну речовин в організмі вагітних корів протягом вагітності. Мета роботи полягала у вивченні особливостей білкового обміну у глибокотільних корів за різних сезонів року. Об’єктом для дослідження слугували корови з молочною продуктивністю 5–6 тис. кг за лактацію на 8–9-му місяці вагітності та відібрані від них зразки крові. Встановлено, що сезонні зміни білкового обміну глибокотільних корів мали циклічний характер. У зимовий період у плазмі крові корів спостерігали зниження вмісту глобулінів (за рахунок -, - і -глобулінів) у порівнянні з літнім, що характеризує високу активність білкового обміну в літній період зі спадом у зимній час. У сухостійних корів вміст альбумінів і білковий коефіцієнт досягали максимуму взимку з достовірним зниженням їх весною та влітку, а восени вони знову мали тенденцію до підвищення. Ступінь і направленість змін активності АЛТ і АСТ подібні сезонним змінам вмісту альбумінів, що свідчить про низьку інтенсивність білоксинтезууючих процесів у печінці в літню пору. The study of the metabolism in the body of cows, depending on the physiological state, factors of feeding and the conditions of content in different seasons of the year, is a necessary condition for the direct effect on their reproductive capacity and productivity. In particular, the scientific and practical interest is the disclosure of physiological and biochemical mechanisms, which are associated with the characteristics of metabolism in the body of cows during pregnancy. The purpose of the research was to study the features of protein metabolism in highly productive deepcalving cows in different seasons of the year. The object for the study is served cows with milk production of 5-6 thousand kg for lactation at 8-9 months of pregnancy and blood samples taken from them. Biochemical study of cows blood plasma was carried out according to generally accepted methods. The recorded seasonal changes in protein exchange of deep-calving cows (Table) were cyclic. In contrast to the total protein content, seasonal differences in its fractional composition were also detected. The dynamics of the change in protein ratio is similar to that of albumin. During the summer, the content of a-globulins increased by 20,1%, b-globulins by 17,3%, g-globulins per 20,5% compared with the spring period. In dry-bodied cows, the activity of ALT and AST in winter increases, reaching its maximum value but in the summer activity of ALT significantly decreased, and its activity was even less than the physiological limits. ACT activity was the lowest in the autumn. Determined that seasonal changes in the protein metabolism of dry cows were cyclic character. A decrease in the content of globulins (due to -, - and -globulins) was observed during the winter period compared to the summer period. This characterizes the high activity of protein metabolism in the summer with the decline in winter. In dry cows, the albumin content and protein ratio reached a maximum in winter with a significant decrease in spring and summer, and in the autumn they again started to rise. The degree and direction of changes in ALT and AST activity were similar to seasonal changes in albumin content. This indicates a low intensity of protein-synthesizing processes in the liver in summer.
Особливості білкового обміну у високопродуктивних глибокотільних корів у різні сезони року
Features of protein metabolism in highly productive dry cows in different seasons of the year
Корейба Людмила Володимирівна https://orcid.org/0000-0002-8658-1779 Дуда Юлія Вікторівна https://orcid.org/0000-0003-0892-0402
Keywords: сезони року; seasons of the year; корови; cows; сухостійний період; dry period; плазма крові; blood plasma; білковий обмін; protein metabolism